2021
DOI: 10.1186/s12890-021-01733-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of the “small plateau” sign on the flow-volume curve followed by deep learning automated recognition

Abstract: Background Small plateau (SP) on the flow-volume curve was found in parts of patients with suspected asthma or upper airway abnormalities, but it lacks clear scientific proof. Therefore, we aimed to characterize its clinical features. Methods We involved patients by reviewing the bronchoprovocation test (BPT) and bronchodilator test (BDT) completed between October 2017 and October 2020 to assess the characteristics of the sign. Patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Esophageal compression can lead to changes in lung function parameters and the appearance of a plateau in the flow-volume curve [12,29]. A plateau on the spirometry flowvolume curve was verified in 38 of our patients.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Esophageal compression can lead to changes in lung function parameters and the appearance of a plateau in the flow-volume curve [12,29]. A plateau on the spirometry flowvolume curve was verified in 38 of our patients.…”
Section: Discussionsupporting
confidence: 60%
“…Extrinsic tracheal compression of the dilated esophagus on the bronchial tree in patients with achalasia may cause a flattened expiratory flow-volume loop in the spirometry test. This plateau in the flow-volume curve is proof of intrathoracic disorder [12]. Several studies have showed that after operation, the asthmatic-like symptoms disappeared; the spirometry findings in pulmonary volumes improved, and in the flow-volume loop, improvements were found [13].…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, we only explored the conventional patterns. Specific patterns, such as upper airway obstruction (Fiorelli et al, 2019), "saw-tooth sign" (Bourne et al, 2017), and the "small-plateau sign" (Wang et al, 2021), require the recognition of flow-volume curves, including inspiratory and expiratory phases.…”
Section: Discussionmentioning
confidence: 99%
“…BDTs were performed using the MasterScreen-Pneumo PC (Jaeger, Germany) and QuarkPFT (COSMED, Italy) spirometers (Wang et al, 2021). All test procedures and results interpretation were performed by trained technicians based on the American Thoracic Society and European Respiratory Society guidelines (Pellegrino et al, 2005;Graham et al, 2019).…”
Section: Bronchodilator Testsmentioning
confidence: 99%